Implementasi Game Educaplay untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Keragaman Budaya Indonesiaku di Kelas 5 SDN Banjaran 4 - Pungky Selvia Taurista; Lusi Noviana Dewi; Alifvia Novita Putri Romadhoni; Mirza Sheila Sofiana; Dzulhijatul Awalin Zuroida; Anik Puji Rahayu; Nurita Primasatya (Jurnal Simki Postgraduate, 2024)
This study aims to implement educaplay as an educational game used as a learning medium to improve students' learning outcomes on the topic "The Cultural Diversity of My Indonesia" in the fifth grade of SDN Banjaran 4. Student learning outcomes are still relatively low, with an average of only 70. Students also appear less active in learning. The use of innovative learning media such as educational games is expected to be a means to improve student learning outcomes. This type of research is classroom action research. Data collection was carried out by tests and observations. Data were analyzed using descriptive quantitative methods. The results of this study showed an increase in student learning outcomes. In cycle I, the average student score was 76.67 with a classical completion rate of 66.67%. While in cycle II, student learning outcomes increased significantly, with an average score reaching 91.11 with classical completion reaching 81.48%. It can be seen that the average learning outcomes from cycle I to cycle II increased by 14.81%.